Mercy Watson fights crime - DiCamillo, Kate; Van Dusen, Chris (Cambridge, Mass. : Candlewick Press, 2006)
Mercy the pig's love of buttered toast leads to the capture of a small thief who would rather be a cowboy.
Ages 6-8.
390
Accelerated Reader AR
Keywords: Swine -- Juvenile fiction; Burglary -- Juvenile fiction; Humorous stories